Arctic Stratosphere Circulation Changes in the 21st Century in Simulations of INM CM5 - Pavel N. Vargin; Sergey V. Kostrykin; Evgeni M. Volodin; Alexander I. Pogoreltsev; Ke Wei (Atmosphere, 2021)
Simulations of Institute of Numerical Mathematics (INM) coupled climate model 5th version for the period from 2015 to 2100 under moderate (SSP2-4.5) and severe (SSP5-8.5) scenarios of greenhouse gases growth are analyzed to investigate changes of Arctic polar stratospheric vortex, planetary wave propagation, Sudden Stratospheric Warming frequency, Final Warming dates, and meridional circulation. Strengthening of wave activity propagation and a stationary planetary wave number 1 in the middle and upper stratosphere, acceleration of meridional circulation, an increase of winter mean polar stratospheric volume (Vpsc) and strengthening of Arctic stratosphere interannual variability after the middle of 21st century, especially under a severe scenario, were revealed. March monthly values of Vpsc in some winters could be about two times more than observed ones in the Arctic stratosphere in the spring of 2011 and 2020, which in turn could lead to large ozone layer destruction. Composite analysis shows that “warm” winters with the least winter mean Vpsc values are characterized by strengthening of wave activity propagation from the troposphere into the stratosphere in December but weaker propagation in January–February in comparison with winters having the largest Vpsc values.